2006
DOI: 10.1002/sia.2255
|View full text |Cite
|
Sign up to set email alerts
|

XPS and contact angle study of N2 and O2 plasma‐modified PTFE, PVDF and PVF surfaces

Abstract: Poly tetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF) and polyvinyl fluoride (PVF) polymer surfaces were exposed to a remote N 2 or O 2 r.f. plasma. The effect of the plasma power and treatment time on the surface energy and the surface composition were studied by static water contact angle (WCA) and X-ray photoelectron spectroscopy (XPS). In every case, a strong defluorination of the surface was observed. Except for PTFE treated by oxygen, all the surfaces became more hydrophilic after plasma treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 6 publications
5
65
0
Order By: Relevance
“…[13] Plasma treatment has been used to promote surface modifications on PVDF. [7,[13][14][15][16][17][18][19][20] Duca et al [21] investigated the surface modifications of PVDF under RF Argon (Ar) plasma, and the results showed an improvement of the PVDF surface wettability under plasma exposure. The surface of PVDF can be also modified by Ar, He (helium) and O 2 (oxygen) plasma, however, oxygen plasma was not effective in decreasing the contact angle of PVDF sheet surface.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Plasma treatment has been used to promote surface modifications on PVDF. [7,[13][14][15][16][17][18][19][20] Duca et al [21] investigated the surface modifications of PVDF under RF Argon (Ar) plasma, and the results showed an improvement of the PVDF surface wettability under plasma exposure. The surface of PVDF can be also modified by Ar, He (helium) and O 2 (oxygen) plasma, however, oxygen plasma was not effective in decreasing the contact angle of PVDF sheet surface.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Vandencasteele et al showed that the treatment of PVF and PVDF surfaces by a O2 discharge at low pressure, led to similar WCA for the treated PVF surfaces (almost 25°) whereas lower WCA were obtained for the PVDF surfaces (around 10°) [39]. In this last case, the reason can be attributed to the highest content of oxygenated functions on the PVDF surface than in the present case (22% for Vandencasteele et al, while 11.2% in our study).…”
Section: Influence Of the O2 Flow Ratementioning
confidence: 99%
“…Therefore, twelve cases have to be considered and for each one, table 1 reports the relative surface composition of the native surface (row 'native'), the surface treated by a helium post-discharge (row 'He') and the surface treated by a helium-oxygen post-discharge (row 'He-O2'). The binding energies of the identified functions can easily be found in the literature [30,31,[36][37][38][39]. The survey of the native HDPE polymer is represented by the black curve in figure 6.…”
Section: Note: This Document Is a Pre-print Version You May Use It Amentioning
confidence: 99%
“…For example, in the experiments by Piperno et al, 37 Teflon was irradiated with high pressure oxygen plasma prior to contact charging, which likely changed the surface composition. For comparison, it was found by Vandencasteele 38 et al that irradiation of Teflon with ten times weaker oxygen plasma for a much shorter time increased the surface oxygen level from 0 to 5%, decreased the surface fluorine from 66 to 36%, and increased the surface carbon from 34 to 59%.…”
Section: The Case For Electron Exchangementioning
confidence: 97%